Securing our children's future: new approaches to juvenile justice and youth violence - Katzmann, Gary S. (Brookings Institution Press, 2002)
Introduction : issues and institutions / Gary S. Katzmann -- New trends in prosecutors' approaches to youthful offenders / Catherine M. Coles and George L. Kelling -- The defense attorney's perspective on youth violence / Barbara Fedders, Randy Hertz, and Stephen Weymouth -- Youth violence : response of the judiciary / David B. Mitchell and Sara E. Kropf -- Managing the juvenile offender population through classification and programming / Gerald G. Gaes -- Reinventing probation and reducing youth violence / Ronald P. Corbett -- An umbrella of legitimacy : Boston Police Department-ten-point coalition collaboration / Jenny Berrien and Christopher Winship -- A tale of one city : reflections on the Boston gun project / David M. Kennedy -- Safety first : partnership, the powerful neutral convener, and problem-solving / Frank Hartmann -- Youth violence, schools, and management : a personal reflection across the sectors / Amalia V. Betanzos -- Media violence : effects and potential remedies / Ronald G. Slaby -- Creating networks of capacity : the challenge of managing society's response to youth violence -- Mark H. Moore -- Conclusion : a new framework and agenda -- Gary S. Katzmann.